Numerical simulation of two–phase separation in a small diameter ratio T‐junction: Numerische Simulation der Zweiphasentrennung in einem T‐Knoten mit kleinem Durchmesser. Issue 3 (April 2017) - Pao, W.; Saieed, A.; Hashim, F. M.; Norpiah, R. B. M.
Abstract: The utilization of T‐junctions for flow division is quite common in industries. Due to the phenomena known as multiphase maldistribution, occurring in a T‐junction, they are often used as partial phase separators for reducing the work load on phase separation devices in oil and gas platforms. Previous literature says that reducing the diameter ratio of the T‐junction improves the two‐phase separation, however it was also reported that reducing the diameter ratio too much has a negative effect on two‐phase separation. To test this, a numerical study was performed to see the two‐phase stratified flow separation in 1, 0.6 and 0.167 diameter ratio T‐junctions. Furthermore, the impact of air superficial velocity on phase maldistribution at the junction is also considered. The T‐junctions with diameter ratios 1 and 0.6 were just used for the validation of present model, by comparing the obtained numerical results with previous experimental data. While, 0.167 diameter ratio T‐junction is the one for which the actual analysis was performed. It is concluded that an increase in air superficial velocity aids liquid carryover, whereas liquid carryover is very sensitive to side arm extraction rates in a very small diameter ratio T‐junction.